The clinical features and perfusion density in paracentral acute middle maculopathy by optical coherence tomography angiography study - Zhengfeng Liu; Xuemei Pan; Dan Wang; Yingying Zou; Peipei Liu; Ying Wang; Hongsheng Bi; Xiaofeng Xie (Photodiagnosis and Photodynamic Therapy)
Purpose: To observe the clinical features of the paracentral acute middle maculopathy (PAMM) and to investigate the changes in perfusion density of superficial capillary plexus (SCP) and deep capillary plexus (DCP) in PAMM by optical coherence tomography angiography (OCTA). Methods: Twelve patients (12 eyes) diagnosed with PAMM and 13 healthy participants (13 eyes) were enrolled. The clinical features of 12 PAMM patients were recorded. The perfusion density of SCP and DCP in the parafovea and perifovea (divided into Temporal, Superior, Nasal, and Inferior) was measured by OCTA in PAMM and healthy eyes. Automated macular maps, including SCP and DCP, were also performed. Results: The mean age of patients was 48.08 (range 14–72) years. The best corrected visual acuity (BCVA) was from finger count (FC) to 1.0. Risk factors included hypertension, diabetes mellitus, COVID-19, etc. The patients had signs of retinal vascular disease except for one patient with isolated PAMM. A spectral-domain OCT image of the PAMM eye showed hyperreflectivity in the inner nuclear layer (INL). Compared with healthy eyes, SCP and DCP in PAMM eyes were significantly reduced in all sectors (all p < 0.05) in the parafovea and perifovea. The average perfusion density of SCP in parafovea and perifovea in PAMM eyes were 46.94±4.34% vs 52.21±3.98 % (p = 0.002), 44.01±3.95% vs 50.51±3.14 (p = 0.000) in healthy eyes. The average perfusion density of DCP in parafovea and perifovea in PAMM eyes were 51.22±4.16% vs 57.15±3.87 % (p = 0.002), 47.375±6.23% vs 54.27±5.33 % (p = 0.002) in healthy eyes. Conclusion: PAMM often accompanies concurrent ocular and systemic diseases. OCTA results confirm that the perfusion density of SCP and DCP in the parafovea and perifovea significantly reduced in PAMM patients.